Injury pattern and risk factors in grassroots football: A study of 10-year-old athletes - Leo Ferdinand; Yulingga Nanda Hanief; Randy M. Manimtim (Sport, Exercise, and Injury, 2025)
Background: Young football players, especially in grassroots competitions, are highly susceptible to injury due to physical contact, fatigue, and underdeveloped motor skills, making injury prevention a critical aspect of early childhood sports. Objectives: This study aims to analyze the types, causes, and needs for injury prevention in 10-year-old football players. Methods: A descriptive quantitative design was used with the survey method. Data was collected through a structured questionnaire distributed to players injured during the competition. A purposive sampling technique was applied with inclusion criteria: (1) players injured during the match and (2) willing to participate. The final sample consisted of 25 athletes. Results: A total of 25 injury incidents were recorded. The most common type of injury was contusion, reaching 13 cases (52%), followed by muscle cramps (20%) and sprains (8%). Most injuries (64%) occurred in the lower extremities, especially the knee and thigh. Injuries predominantly occurred in the second half of matches (60%), with 88% caused by physical contact with an opponent. In the absence of medical personnel, coaches often found themselves in the role of first responders, a challenging position that requires adequate training and support. Many players continued to play despite their injuries, indicating a need for improved injury management. Conclusions: The study concluded that football injuries in children generally occur in the lower extremities, with bruising being the most dominant type. Player-to-player collisions caused most injuries, and many players could continue the match. This shows the importance of prevention, education, and follow-up for developing the sport of football.